Heat exchange efficiency and structural stability of assembled energy shafts: a novel shallow geothermal exploitation system for coastal urban cities - Jie Zhou; Xin Wang; Jie Xu; Zhenming Shi (Geothermal Energy)
Abstract As a crucial solution to the challenge of limited urban underground space development, the assembled shaft offers extensive structure–soil contact surfaces and meantime holds significant potential for shallow geothermal energy exploitation. In this paper, we propose an assembled energy shaft, i.e. a novel geothermal development system, in which the heat exchanger could be easily installed in the shaft concrete with extensive soil–contact area and can have superior protection without extra pre-drilling. This paper establishes a heat transfer model for energy shafts in soft soil areas. By comparing the heat transfer efficiency and additional thermal stress of the energy tunnel in Beijing, the practical feasibility of constructing energy shafts in coastal cities is demonstrated. By proposing the characterization parameters of heat exchange capacity per unit lining surface area and heat exchange per unit length of pipe, it is revealed that thermal interference is minimized when the heat exchange pipe spacing of the energy shaft is 0.25–0.3 m. The heat exchange efficiency is increased when the fluid flow rate is 0.6 m/s ~ 0.9 m/s. According to the deformation characteristics of the lining, the maximum tensile and compressive stresses occur near the inlet of the heat exchange pipe. To minimize stress concentration, it is advisable to position the inlet of the heat exchange pipe at the center of the segment. The research findings confirm the substantial potential of assembled energy shafts in shallow geothermal development and provide valuable insights for the design of such shafts in coastal cities.